Forecasting the onset date of southwest monsoon over Delhi - SINGH , DHANNA; GOYAL, SUMAN (MAUSAM, 1998)
Using latest 32 years (1964-95) data, upper air temperatures and zonal and meridional components of winds of several selected stations for various standard isobaric levels (850 to 10 hPa) are screened for the pre-monsoon months of April & May in order to study their association with onset date of southwest monsoon at Delhi. Data for temperature and wind components for May for several stations exhibit significant correlations with onset-date. Some well known parameters presently in use in long range forecast models of monsoon seasonal rainfall have also been screened similarly. With a multiple regression technique, equations have been developed using suitable parameters from those which showed significant linear correlations.